Enhancing Indoor Thermal Comfort and Energy Efficiency in Residential Buildings of Hot Humid Region of Nepal – A Case of Biratnagar Metropolitan City - Chaulagain, Nischal; Shah, Malesh; Baral, Bivek (Kathmandu University Journal of Science, Engineering and Technology, 2021)
Essence of indoor thermal comfort and reduction of active power consumption to meet indoor thermal needs has been a keen interest of academia around the globe which has resulted into formulation of strict guidelines for indoor environment requirements in developed countries. Nepal on the other hand lacks the basic provisions when it comes to assuring indoor comfort. Studies shows that unscientific building construction has caused people to depend on changing food and clothing habits to accommodate to the present scenario of indoor environment. The main aim of this study is to address this underlying issue through passive interventions such that both indoor thermal comfort and energy efficiency can be achieved. The study is based on evaluating the effects of various passive and energy efficient building technologies on indoor thermal environment through building energy modeling using EnergyPlus computational engine. Present scenario of indoor thermal environment of residential buildings at Biratnagar and retrofitting measures including insulation, glazing variants, shading, air tightness and others that can enhance indoor thermal comfort whilst enhancing energy efficiency is presented in this paper. In present context, the indoor thermal comfort as indicated by ASHRAE (American Society of Heating Refrigeration and Air Conditioning Engineers) 55 Adaptive Model 80% Acceptability limits is only 32% of total hours in a year, i.e. indoor comfort is compromised for above 5800 hours (equivalent to 8 months) with `hot' to `sweltering' indoor environment. Effects of 8 passive design interventions on residential building was analyzed based on the thermal load reduction potential and increase in acceptable limits of indoor comfort hours. It was found that combination of various design changes would help achieve up to 86% indoor thermal comfort hours and reduce annual thermal load by 68% relative to the base case scenario The study shows that incorporating passive techniques on Nepalese residential buildings can assure indoor comfort and reduce active heating/cooling demand.